2012
DOI: 10.1158/1535-7163.mct-12-0095
|View full text |Cite
|
Sign up to set email alerts
|

ATP Citrate Lyase Knockdown Induces Growth Arrest and Apoptosis through Different Cell- and Environment-Dependent Mechanisms

Abstract: ATP citrate lyase (ACLY) is a cytosolic enzyme that catalyzes generation of acetyl-CoA, which is a vital building block for fatty acid, cholesterol, and isoprenoid biosynthesis. ACLY is upregulated in several types of cancer, and its inhibition induces proliferation arrest in certain cancer cells. As ACLY is involved in several pathways, its downregulation may affect multiple processes. Here, we have shown that short hairpin RNAmediated ACLY silencing in cell lines derived from different types of cancers induc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 40 publications
3
91
0
Order By: Relevance
“…Increased de novo lipogenesis is a key characteristic of rapidly proliferating cancer cells, in which conversion of cytosolic citrate into acetyl-CoA and oxaloacetate by ACLY represents the initial and rate-limiting step for the biosynthesis of long-chain fatty acids and cholesterol as building blocks for cell growth (29,30). In the liver, the level of cytosolic citrate is well-maintained through CIC-mediated export from the TCA cycle in mitochondria and SLC13A5-mediated uptake from the circulation (24,31).…”
Section: Discussionmentioning
confidence: 99%
“…Increased de novo lipogenesis is a key characteristic of rapidly proliferating cancer cells, in which conversion of cytosolic citrate into acetyl-CoA and oxaloacetate by ACLY represents the initial and rate-limiting step for the biosynthesis of long-chain fatty acids and cholesterol as building blocks for cell growth (29,30). In the liver, the level of cytosolic citrate is well-maintained through CIC-mediated export from the TCA cycle in mitochondria and SLC13A5-mediated uptake from the circulation (24,31).…”
Section: Discussionmentioning
confidence: 99%
“…CUL3 inhibits the proliferation and anchorageindependent growth of lung cancer cells through negative regulation of ACLY ACLY plays a critical role in promoting cancer cell proliferation, and targeting ACLY by RNAi or specific small molecule inhibitors such as SB-204990 inhibits proliferation of cancer cells in vitro and in vivo Hatzivassiliou et al 2005;Migita et al 2008;Zaidi et al 2012a). Here, we investigated whether CUL3 inhibits proliferation of lung cancer cells through negative regulation of ACLY in different lung cancer cells as well as normal lung NHBE cells in vitro by MTT assays.…”
Section: Cul3 Inhibits De Novo Lipid Synthesis Through Negative Regulmentioning
confidence: 99%
“…Promoting lipid synthesis is critical for the role of ACLY in tumor progression Hatzivassiliou et al 2005;Migita et al 2008;Zaidi et al 2012a). It has been reported that supplementation of cells with metabolites from the fatty acid synthesis pathway (e.g., oleic acid and palmitic acid) and the mevalonate pathway (e.g., mevalonate and cholesterol) rescued the growth inhibition of cancer cells caused by inhibition of lipid synthesis, including ACLY knockdown (Nakakuki et al 2007;Zaidi et al 2012a;Young et al 2013).…”
Section: Cul3 Inhibits De Novo Lipid Synthesis Through Negative Regulmentioning
confidence: 99%
“…Both ACC and ACL have been found to be over-expressed in many cancers such as breast, liver, lung, ovarian, prostate and leukemia cancers [132,133]. Inhibition of either ACL or ACC induces growth arrest and apoptosis in several cancer cell lines [134][135][136]. The potential mechanism of ACL overexpression in tumorigenesis is through PI3K/AKT and MAPK signaling pathway [135,137].…”
Section: Atp-citrate Lyase and Acetyl Coa Carboxylasementioning
confidence: 99%